Telemedicine in the era of coronavirus 19: Implications for postoperative care in cardiac surgery. Issue 10 (2nd August 2021) - Sallam, Aminah; Shang, Michael; Vallabhajosyula, Ishani; Mori, Makoto; Chinian, Rachel; Assi, Roland; Bonde, Pramod; Geirsson, Arnar; Vallabhajosyula, Prashanth
Abstract: Background: The Coronavirus 19 (COVID‐19) pandemic forced an unprecedented shift of postoperative care for cardiac surgery patients to telemedicine. How patients and surgeons perceive telemedicine is unknown. We examined patient and provider satisfaction with postoperative telehealth visits following cardiac surgery. Methods: Between April 2020 and September 2020, patients who underwent open cardiac surgery and had a postoperative appointment via telemedicine were administered a patient satisfaction survey over the phone. Time of survey administration ranged from 1 to 4 weeks following their appointment. Surgeons also completed a satisfaction survey following each telemedicine appointment they conducted. Results: Fifty patients were surveyed. Of these, 36 (72%) had a postoperative appointment over the telephone, and 14 (28%) had a postoperative appointment via video‐chat. Overall, patients expressed satisfaction with the care that they received via our two telemedicine modalities (mean Likert scale agreement 4.8, SD 0.5). Despite this, 46% of patients said they would prefer their next postoperative appointment to be via telemedicine even if there was not a stay‐at‐home order in place. All surgeons surveyed reported ( agree / strongly agree ) that they would prefer to see their postoperative patients using telemedicine. Conclusions: These findings highlight acceptability of continuing telemedicine use in the postoperative care of cardiac surgery patients.